Bulgaria - Environmental Sequencing Strategies for EU Accession : Priority Public Investments for Wastewater Treatment and Landfill of Waste - World Bank (Washington, DC, 2013)
Despite Bulgaria's progress to act in accordance with European Union (EU) environmental directives, full compliance with the Union's environmental acquis remains a challenge and requires a substantial investment program in environmental infrastructure and implementation activities in pollution abatement, waste management, and financing the associated operation and maintenance costs. The report focuses on financial planning and provides guidance on assessment of the cost implications of adopting the EU Council Directives on urban wastewater treatment and solid waste management. Some of the report recommendation are : planning for the future must reflect a new approach to environmental management, involving constructive cooperation with local communities and neighboring municipalities, and private sector participation to contribute to the delivery of public services; conduct a public awareness campaign to prepare the public to accept new waste management practices; and lastly, prepare a national waste strategy in order to fulfill the EU Waste Directive.